Cultivating Excellence: Moving Beyond Engineering Thinking to Living‐Systems Thinking. Issue 4 (April 2017) - Holliday, Michelle
Abstract : For the past several centuries, Western society has been guided by a mechanistic view of the world and of work. Now, that story is steadily being overtaken by a view of the world not as a predictable machine but as a vibrant, dynamic ecosystem. This shift has profound implications for every field of human endeavor, including performance improvement. Furthermore, embracing this perspective may be critical to the survival of our species.